Extralobar pulmonary sequestration with absence of pericardium and atrial septal defect in a woman - Zhenhuan Tian; Yuncan Zhou; Hongsheng Liu (Journal of Cardiothoracic Surgery, 2019)
Abstract Background Extralobar sequestration is a rare congenital malformation of lung tissue, which can be combined with other foregut and cardiac abnormalities. Our case is the first to report extralobar sequestration, absence of pericardium and atrial septal defect in the same patient. Case presentation A 22-year-old female with atrial septal defect came for her recent atypical symptom of intermittent palpitation and shortness of breath. Her computed tomography showed a cystic mass located in left superior anterior mediastinum near the pulmonary trunk. With specious of cystic teratoma prior to video-assisted thoracoscopic surgery, she finally was diagnosed as extralobar sequestration, while incidentally found with congenital absence of pericardium during surgery. Conclusions Extralobar sequestration, absence of pericardium and atrial septal defect can occur in the same patient. The preoperative diagnostic rate of extralobar sequestration and asymptomatic absence of pericardium remains low attributed to atypical imaging features. A cardiac magnetic resonance imaging is highly recommended if necessary. Regular follow-up is essential to asymptomatic absence of pericardium and atrial septal defect patients. To patients with extralobar sequestration, an operation could be performed.